2008
DOI: 10.1080/10428190701861686
|View full text |Cite
|
Sign up to set email alerts
|

Novel anti-myeloma agents and angiogenesis

Abstract: During the last decade several novel agents have been used in the management of patients with multiple myeloma. Immunomodulatory drugs and proteasome inhibitors exert their efficacy both directly by inducing apoptosis of myeloma cells and indirectly through the interruption of the interactions between myeloma and stromal cells in the bone marrow (BM) microenvironment. These interactions are crucial for myeloma cell growth and survival. The adherence of myeloma cells to BM stromal cells leads to the overproduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
30
0
8

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 105 publications
2
30
0
8
Order By: Relevance
“…Similarly, it has been shown that Bortezomib at clinically achievable concentrations inhibits endothelial cell proliferation and targets VEGFinduced caveoln-1 phosphorylation in endothelial cells [134]. Bortezomib also blocks MM interaction with BM stromal cells and indirectly blocks the production of proangiogenic factors [125]. Pre-clinical in vivo studies confirm the potential anti-angiogenic effect of the proteasome inhibitors [135] and it has been consistently reported that MM patients treated with Bortezomib show a significant reduction in MVD although serum VEGF are not consistently reduced [136].…”
Section: Anti Angiogenic Effect Of the Novel Anti-mm Agents And Futurmentioning
confidence: 95%
See 3 more Smart Citations
“…Similarly, it has been shown that Bortezomib at clinically achievable concentrations inhibits endothelial cell proliferation and targets VEGFinduced caveoln-1 phosphorylation in endothelial cells [134]. Bortezomib also blocks MM interaction with BM stromal cells and indirectly blocks the production of proangiogenic factors [125]. Pre-clinical in vivo studies confirm the potential anti-angiogenic effect of the proteasome inhibitors [135] and it has been consistently reported that MM patients treated with Bortezomib show a significant reduction in MVD although serum VEGF are not consistently reduced [136].…”
Section: Anti Angiogenic Effect Of the Novel Anti-mm Agents And Futurmentioning
confidence: 95%
“…Firstly it was demonstrated that thalidomide inhibits bFGF by a rabbit corneal assay [124]. Others showed that thalidomide inhibits VEGF, HGF, bFGF, IGF-1 and Ang-2 expression by BM endothelial cells isolated from MM patients [125,126]. All IMiDs, including lenalidomide and pomalidomide, have anti-angiogenic activity independent of their immunomodulatory effects [125,127,128], although thalidomide is probably a more prominent inhibitor of angiogenesis than its derivatives.…”
Section: Anti Angiogenic Effect Of the Novel Anti-mm Agents And Futurmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the use of THD during pregnancy led to phocomelia and consequently the drug was withdrawn from the market (17). Subsequent studies have reported that THD has anti-inflammatory, immunomodulatory and anti-angiogenic effects (18)(19)(20)(21)(22). Due to its anti angiogenic effects, THD is able to affect fetal development in pregnant women, which leads to fetal deformity.…”
Section: Introductionmentioning
confidence: 99%